Risk factors associated with oral and maxillofacial benign tumors: A case-control study - Fang, H-J. (Cellular and Molecular Biology, 2017)
This study aimed to investigate the risk factors for oral and maxillofacial benign tumors (OMFBTs). A total of 138 patients diagnosed with OMFBTs between September 2010 and September 2015 were retrospectively analyzed. Clinical data including demographic characteristics, smoking and drinking status, dietary habit, oral hygiene and tumor related family history were collected and compared with 134 cases of healthy people who visited the hospital for physical examination during the same time. Logistic regression analysis was performed for multivariable regression analysis. OMFBTs was associated with smoking more than 20 cigarettes per day, accumulated cigarette consumption more than 30, accumulated cigarette package consumption more than 1000, present smoking and drinking, passive smoking before 18 years old, initial smoking age more than 20 years old and alcohol consumption more than 50 g/d (P < 0.05). Consumption of meat, fish, seafood, fruits and vitamin tablets were associated with lower risk of OMFBTs. Non-conditional logistic regression analyses indicated that the independent risk factors of OMFBTs included accumulated cigarette consumption, passive smoking before the age of 18, meat-free, fish-free, fruit-free, vitamin tablets-free, frequency of tooth brushing lower than once a day, not routinely attending oral examination, wearing denture and drinking alcohol (P < 0.05). Smoking and drinking should be discouraged in dental patients. Keeping a good dietary habit and routinely attending oral examination are highly encouraged.